2022
DOI: 10.3390/cancers14092063
|View full text |Cite
|
Sign up to set email alerts
|

KRAS Mutations Impact Clinical Outcome in Metastatic Non-Small Cell Lung Cancer

Abstract: There is an urgent need to identify new predictive biomarkers for treatment response to both platinum doublet chemotherapy (PT) and immune checkpoint blockade (ICB). Here, we evaluated whether treatment outcome could be affected by KRAS mutational status in patients with metastatic (Stage IV) non-small cell lung cancer (NSCLC). All consecutive patients molecularly assessed and diagnosed between 2016–2018 with Stage IV NSCLC in the region of West Sweden were included in this multi-center retrospective study. Th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 46 publications
2
16
1
Order By: Relevance
“…We observe that TP53 mutation status is associated with resistance to three drugs, concordant with earlier observations showing that TP53 mutant are more resistant to chemotherapy [14]. Resistance to Gemcitabine and Vincristine is also associated with KRAS and PI3KCA mutations, known for their proliferative potential [18,10]. Interestingly, mutations in MYC and MAPK8IP2 are associated with sensitivity to these three drugs.…”
Section: Study Of Genes Contributing To the Joint Signalssupporting
confidence: 90%
“…We observe that TP53 mutation status is associated with resistance to three drugs, concordant with earlier observations showing that TP53 mutant are more resistant to chemotherapy [14]. Resistance to Gemcitabine and Vincristine is also associated with KRAS and PI3KCA mutations, known for their proliferative potential [18,10]. Interestingly, mutations in MYC and MAPK8IP2 are associated with sensitivity to these three drugs.…”
Section: Study Of Genes Contributing To the Joint Signalssupporting
confidence: 90%
“…Interestingly, among these genes, the highest number of genetic interactions were found for KRAS (Fig. 3E), which had important roles in the occurrence and development of diverse cancers [37,38]. These findings confirmed a crucial role and great potential application of KRAS in synthetic lethality.…”
Section: Expression Profiles Of Involved Genessupporting
confidence: 61%
“…KRAS mutation is the most prevalent oncogenic driver in NSCLC (35%) but the prognostic and predictive role of KRAS mutations is under debate. While we and others have shown KRAS mutations to negatively influence the prognosis of NSCLC, 12-15 some studies found no difference in OS. 16-18 In addition, some have reported shorter OS for KRAS MUT compared to wild type (KRAS WT ) patients following first-line platinum-based chemotherapy.…”
Section: Introductioncontrasting
confidence: 53%
“…The predictive role of KRAS mutation in relation to outcome in NSCLC is a controversial topic, particularly for stage III NSCLC where the literature is relatively sparse in contrast to earlier stages and metastatic stage IV disease. In the latter, treated with chemotherapy, some studies describe KRAS mutation as a negative prognostic factor for OS and PFS [13][14][15] while others demonstrate an equal survival benefit for KRAS MUT and KRAS WT patients [16][17][18] . After the introduction of ICB in the stage IV treatment paradigm new assessment of the impact of KRAS have been performed but do not consistently point in the same direction, and the predictive value of KRAS related to ICB treatment remains debatable.…”
Section: Discussionmentioning
confidence: 99%